先化简再求值,已知a=﹣2,b=﹣1,c=3,求代数式5abc﹣2a 2 b﹣[(4ab 2 ﹣a 2 b)﹣3abc]
1个回答
原式=5abc﹣2a
2
b﹣4ab
2
+a
2
b+3abc=8abc﹣a
2
b﹣4ab
2
;
a=﹣2,b=﹣1,c=3时,原式=8 ×2 ×1×3﹣4 ×(﹣1)﹣4 ×(﹣2)×1=60.
相关问题
先化简再求值,已知a=-2,b=-1,c=3,求代数式5abc-2a2b-[(4ab2-a2b)-3abc]的值.
先化简再求值5abc-{2a2b-[3abc-(4ab2-a2b)]-2ab2},其中a=-2,b=3,c=-[1/4]
先化简再求值5abc-{2a2b-[3abc-(4ab2-a2b)]-2ab2},其中a=-2,b=3,c=-[1/4]
先化简,再求值:5abc-2a2b-[3abc-(4a2b-a2b)],其中a=2,b=3,c=-1.
先化简,再求值:5abc-2a2b-[3abc+2(2ab2-a2b)],其中a=−12,b=-1,c=3.
先化简再求值:5abc﹣{2a 2 b﹣[3abc﹣(4ab 2 ﹣a 2 b)]﹣2ab 2 },其中a=﹣2,b=3
先化简,再求值.已知a+b=1,ab= 2 9 ,求代数式a 3 b-2a 2 b 2 +ab 3 的值.
先化简再求值:3a^2b-[2a^2b-(2abc-a^2b)-4a^2c]-abc,其中a=-2,b=-3,c=1
先化简再求值:-1/2a^2b-[3\2a^2b-3(abc-1\3a^2c)-4a^2c]-3abc,其中a=-1,b
已知a=-2,b=-1,c=3,求代数式5abc-2a2b+[3abc-(4ab2-a2b]的值.